Strategi menumbuhkan Emotional Intelligence guna meningkatkan kepuasan kerja - Sadewo, Mohammad Tio Pangku (Maliki Interdisciplinary Journal, 2024)
This article aims to assist readers in gaining literacy related to the cultivation of emotional intelligence in enhancing job satisfaction. Job satisfaction is an important factor in individual success and well-being in the workplace. When someone feels satisfied with their job, they tend to be more motivated, productive, and have an overall better quality of life. Some ways to cultivate emotional intelligence include improving self-control, enhancing resilience when facing problems, increasing self-motivation, improving mood and empathy, and enhancing relationships with others.